A novel discrete differential evolution algorithm - Lingjuan HOU; Zhijiang HOU (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the stochastic vehicle routing problems with simultaneous pickups and deliveries, a novel discrete differential evolution algorithm is proposed for routes optimization. The algorithm can directly be used for the discrete domain by special design. Computational simulations and comparisons based on two kinds of problems of different sizes of SVRPSPD are provided. Results demonstrate that the proposed algorithm obtains better results than the basic differential evolution algorithm and the existing genetic algorithm. http://dx.doi.org/10.11591/telkomnika.v11i4.2346